2016
DOI: 10.18632/oncotarget.11609
|View full text |Cite
|
Sign up to set email alerts
|

Superior anti-tumor efficacy of diisopropylamine dichloroacetate compared with dichloroacetate in a subcutaneous transplantation breast tumor model

Abstract: Dichloroacetate (DCA), an inhibitor of pyruvate dehydrogenase kinase, has anti-tumor properties in various carcinoma models. Diisopropylamine dichloroacetate (DADA), an over-the-counter drug for chronic liver disease, is a derivative of DCA. To date, few studies have evaluated the anticancer potential of DADA in breast cancer. In this study, MDA-MB-231 cells, a breast adenocarcinoma cell line, were used in in vitro and in vivo experiments to evaluate the anti-tumor efficacy of DADA and DCA. The half maximal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Intriguingly, the PDKs' pan‐inhibitor dichloroacetate and PDK4's specific inhibitor diisopropylamine dichloroacetate (DADA) exhibit antitumor efficacy in breast cancer models by inducing cell death . In this regard, PDK4 inhibitors might be particularly useful in triggering cell death in HCC and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the PDKs' pan‐inhibitor dichloroacetate and PDK4's specific inhibitor diisopropylamine dichloroacetate (DADA) exhibit antitumor efficacy in breast cancer models by inducing cell death . In this regard, PDK4 inhibitors might be particularly useful in triggering cell death in HCC and other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dichloroacetate (DCA) is a pyruvate dehydrogenase kinase inhibitor with anti-tumor activity in a variety of carcinomas. Studies have also indicated that diisopropylamine dichloroacetate (DADA) could ameliorate the metabolism of hepatocytes in chronic liver disease [165]. In a study by Yamane et al attempting to evaluate the effect of DADA on influenza-infected mice (PR8), oral administration of DADA was found to not only restore the activity of PDH and ATP in affected organs but also suppress cytokine storm and viral replication [94].…”
Section: Novel Therapeutic Approaches By Targeting Metabolic Pathwaysmentioning
confidence: 99%
“…Experimental human cancer xenograft studies in vivo with the DCA treatment monotherapy has been found to have antitumor properties in non-small cell lung cancer [83,170,171], lung adenocarcinoma [172], breast adenocarcinoma [171,173], colorectal cancer [174,175], neuroblastoma [176], glioblastoma [177], pancreatic cancer [178,179], hepatocellular carcinoma [53,180], and ovarian adenocarcinoma [181]. Other researchers found that DCA treatment did not exert antitumor activity against xenografted non-small cell lung cancer [170,182], breast adenocarcinoma [9,183], colon and colorectal cancer [184,185,186,187], and glioblastoma [188,189] in vivo (Table 2).…”
Section: Experimental Research Of Dca Monotherapy Efficacy In Cancmentioning
confidence: 99%
“…As shown in Table 2, a remarkable number of papers did not indicate the gender of animals used for research, and this concerns 46.7% of the DCA-treated groups described in the manuscripts. It is understandable when the researchers used female animals for breast or ovary cancer studies [9,173,183], but there was no grounded reason for why they chose to conduct the studies on different genders in other cancer localizations. As shown in Table 2, of all investigated animal groups, the sex was not indicated for 47% of cases.…”
Section: Experimental Research Of Dca Monotherapy Efficacy In Cancmentioning
confidence: 99%